Exploring the Path of Cultivating Employability of Medical College Students under Practice Orientation (Journal of Global Humanities and Social Sciences, 2024)
With the continuous development of the medical industry, the employment situation of medical specialty college students is also gradually intensifying. Therefore, how to improve students' employability and competitiveness through a practice-oriented approach has become a problem that needs to be solved in medical specialty education. This paper proposes a four-point strategy based on practice orientation: providing rich internship and practical training opportunities, carrying out diversified scientific research projects, setting up relevant professional practice courses, and cultivating students' professional ethical qualities, to provide medical students with a perfect program for cultivating their employability and promoting the development and innovation of the medical specialty.